PELATIHAN PEMBUATAN PRODUK UNGGULAN IKAN ASAP MELALUI PENGAPLIKASIAN RUMAH ASAP MODEL KABINET DAN KEMASAN PLASTIK VAKUM - Miftahul Khair Kadim; Nuralim Pasisingi; Sitty Ainsyah Habibie (Universitas Mataram, 2023)
Dulangeya Village is one of the villages in the Coastal District of Botumoito, Boalemo Regency. One of the Village's potentials in the fisheries sector is reef fish (stones) which are sold in fresh form or traditionally processed into hanging dried fish. Traditional drying techniques have weaknesses, especially in terms of product unhygienicity. This community service activity aims to improve the skills of local communities by providing education and training on the process of processing smoked fish through the application of a cabinet model smokehouse and vacuum plastic packaging. This activity was carried out in Dulangeya Village, Botumoito District, Boalemo Regency for 45 days. The training was carried out by providing socialization and education related to processed smoked fish products, followed by practical activities for making smoked fish and packaging. The target group for the activity is the fishermen's wives in Dulangeya Village. Through this activity, the people of Dulangeya Village gained additional skills in making smoked rock fish products typical of Dulangeya. Communities are introduced and given education regarding the smoking process using closed cabinet model smokehouses as an effort to optimize the utilization of trapped heat and smoke. In addition, the closed cabinet construction model is also intended to minimize product direct contact with pollutant sources. The community was also trained and improved their skills in terms of product packaging using vacuum sealers and vacuum plastic as well as packaging labeling, so that smoked rock fish products were produced which were hygienic and attractive. With this activity, the activity partner community has been able to make hygienic smoked rock fish products with vacuum plastic packaging and attractive packaging labels as an innovative product that is expected to improve the local community's economy.